Obsessive-compulsive disorder – A question of conscience? An fMRI study of behavioural and neurofunctional correlates of shame and guilt. (September 2015) - Hennig-Fast, Kristina; Michl, Petra; Müller, Johann; Niedermeier, Nico; Coates, Ute; Müller, Norbert; Engel, Rolf R.; Möller, Hans-Jürgen; Reiser, Maximilian; Meindl, Thomas
Abstract: Shame and guilt can be described as 'self-conscious emotions' and are an essential part of the psychopathology in obsessive-compulsive disorder (OCD). Our primary aim was to explore whether individuals with OCD are processing shame and guilt differently from healthy individuals (N = 20 in both groups; 50% female; age: 20–40 years) on the behavioural and neurobiological level. For the experimental task, participants were scanned with functional magnetic resonance tomography (functional magnetic resonance imaging, 3 T) while imagining neutral, shame inducing and guilt inducing scenarios. In addition to clinical questionnaires, participants were asked to complete questionnaires measuring shame and guilt. The functional data indicate an increased activity in OCD patients in the shame condition in the limbic, temporal and sub-lobar (hypothalamus) areas, in the guilt condition inter alia in frontal, limbic and temporal areas. In summary we found activity in OCD patients in neural networks which are responsible for stimulus filtering, emotion regulation, impulse control and memory. The results from our study may contribute to a better understanding of the origins and maintenance of OCD in association with the pathological processing of shame and guilt on different functional levels. Highlights: Increased activity in OCD in the shame condition in limbic, temporal, sub-lobar areas. Increased activity in OCD in the guilt condition in frontal, limbic, temporal Areas. Neural activity in OCD reflects stimulus filtering, emotion regulation and memory. In OCD increased shame and guilt is experienced.